2023
DOI: 10.1167/iovs.64.7.10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Testing of the Virus-Like Drug Conjugate Belzupacap Sarotalocan (AU-011) on Uveal Melanoma Suggests BAP1-Related Immunostimulatory Capacity

Sen Ma,
Ruben V. Huis In't Veld,
Alexander Houy
et al.

Abstract: Purpose The virus-like drug conjugate belzupacap sarotalocan (AU-011), currently under clinical investigation for first-line treatment of primary uveal melanoma (UM), shows enhanced tumor specificity by targeting heparan sulfate proteoglycans (HSPG). Such a treatment may potentially lead to systemic immune responses. We studied the potential of AU-011 treatment to induce immunogenic cell death as the first step to induce systemic immunity. Methods We determined binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…It is distinctive due to its tumor-targeting capabilities via HSPGs (heparan sulfate proteoglycans), that are overexpressed on tumor cells [ 275 ]. Preliminary AU-011 research showed promise in triggering immunogenic cell death in various UM cell lines [ 276 ]. This treatment appears to work as an immuno-stimulant by increasing the exposure of DAMPs (damage-associated molecular patterns) on the cell membrane, specifically CRT (calreticulin) and HSP90 (heat shock protein 90) [ 276 ].…”
Section: Current and Emerging Therapeuticsmentioning
confidence: 99%
“…It is distinctive due to its tumor-targeting capabilities via HSPGs (heparan sulfate proteoglycans), that are overexpressed on tumor cells [ 275 ]. Preliminary AU-011 research showed promise in triggering immunogenic cell death in various UM cell lines [ 276 ]. This treatment appears to work as an immuno-stimulant by increasing the exposure of DAMPs (damage-associated molecular patterns) on the cell membrane, specifically CRT (calreticulin) and HSP90 (heat shock protein 90) [ 276 ].…”
Section: Current and Emerging Therapeuticsmentioning
confidence: 99%